A Comparison of N-acetyl Aspartate Concentrations between Two Main Subtypes of Multiple Sclerosis using Magnetic Resonance Spectroscopy Imaging - Yadollahpour, Ali (Asian Journal of Pharmaceutics (AJP), 2017)
Background and Objective: Multiple sclerosis (MS) is the most common non-traumatic neurological disorder among young adults. Studies are ongoing to find efficient biomarkers for early and differential diagnosis of different MS subtypes based on neuroimaging techniques, particularly magnetic resonance spectroscopy imaging (MRSI). Relapsing-remitting MS (RRMS) and primary-progressive MS (PPMS) are the two main subtypes of MS often difficult to be differentiated. The present study aims to comparatively assess the concentrations of N-acetyl aspartate (NAA) in RRMS and PPMS patients using MRSI. The concentrations in two regions of the brain including white matter (WM) lesions (plaques) and normal-appearing WM (NAWM) are assessed. Materials and Methods: The MRSI (1.5 T) of the brain of MS patients (n = 28) was performed to determine the relative concentrations of NAA in NAWM and plaque regions and compared between two main MS subtypes of RRMS and PPMS. The images were acquisitioned with point resolved spectroscopy sequence, single voxel mode (24 mm Ã— 24 mm Ã— 24 mm), and repeated time (1500 ms) and echo time (35 ms). The relative concentrations of NAA in NAWM and plaque were compared between two subtypes. Results: The analysis of variance showed no significant difference in NAA of NAWM between PPMS and RRMS (P = 0.06). Similarly, there was no significant difference in NAA levels in the plaque region between PPMS and RRMS groups (P = 0.7). It should be noted that the difference in the concentrations of NAA in NAWM between RRMS and PPMS was higher than the difference between the plaque regions. Conclusion: Our findings showed that the NAA values in NAWM assessed by MRSI may be an adjunctive diagnostic index for differential diagnosis of two subtypes of MS disorder